Navigating the need for mobile apps in higher education: The Mediating role of digital transformation - Adam, Fia Fridayanti; Ferezagia, Debrina Vita; Grataridarga, Niko; Wiwesa, Ngurah Rangga; Mona, Nailul; Altamira, Melisa Bunga; Subarrao, Anusuyah; Khan, Nasreen (Edelweiss Applied Science and Technology, 2026)
In today's fast-paced and interconnected digital era, universities must provide digital academic support services to facilitate effective learning for students. Universitas Indonesia (UI), as part of higher education, has implemented comprehensive academic digitalization, but most of these are web-based. Since mobile apps are growing, the need for such applications has become necessary. This study aims to analyze the digital transformation process of campus support services at UI and assess the need for mobile apps, which are limited to three applications at UI: SIAK-NG, EMAS, and SIGMA. Data collection was obtained through direct surveys distributed to 589 UI Vocational students. Data analysis was conducted quantitatively using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings indicate that digital transformation significantly moderates the relationship between user experience and students' need for mobile apps. The model demonstrates a good fit. It is confirmed that user experience has a significant and positive impact on digital transformation, and digital transformation significantly and positively influences students' need for mobile apps. The need for mobile apps in higher education continues to grow alongside advancements in technology and increasing student expectations for faster, more accessible services.